(untitled) (International journal of artificial intelligence, 2026)
The article presents the results of a study on assessing the dental status and improving the effectiveness of treatment for patients with chronic diffuse liver diseases (CDLP). The study involved 94 patients divided into groups depending on the primary pathology: liver fibrosis, chronic hepatitis, and liver cirrhosis. Two strategies were compared: standard dental care and a comprehensive protocol including the drug "Rotokan," electrophoresis with vitamin C, and UVC therapy. It has been established that the progression of liver diseases correlates with the deterioration of dental indices (GI, PMA, CE). The application of the comprehensive method made it possible to suppress periodontal inflammation twice as quickly, restore enamel resistance, and stabilize the carious process. The study scientifically substantiates the high pathogenetic effectiveness of a multidisciplinary approach combined with physiotherapy for systemic liver disorders.